2018
DOI: 10.1029/2017jb015160
|View full text |Cite
|
Sign up to set email alerts
|

The Electrical Structure of the Central Main Ethiopian Rift as Imaged by Magnetotellurics: Implications for Magma Storage and Pathways

Abstract: The Main Ethiopian Rift is part of the East African Rift with its unique geological setting as an active continental breakup zone. The Main Ethiopian Rift includes a number of understudied active volcanoes with potentially high risks for this densely populated part of Ethiopia. Using newly recorded (2016) magnetotelluric data along a 110 km long transect crossing the whole rift, we present a regional 2‐D model of electrical resistivity of the crust. The derived model endorses a previous study that drew the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 80 publications
6
49
1
Order By: Relevance
“…The lack of regional context presents additional challenges. This is made strikingly clear by the more regional studies of Whaler and Hautot () and Hübert et al (), which model 100‐ to 200‐km‐long profiles extending outside a magmatic rift segment and into tectonically stable crust. Models from both these studies image the most intense conductive features outside the active rift segment, calling into question the magmatic interpretations almost ubiquitously given to conductors within an active volcanic environment.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The lack of regional context presents additional challenges. This is made strikingly clear by the more regional studies of Whaler and Hautot () and Hübert et al (), which model 100‐ to 200‐km‐long profiles extending outside a magmatic rift segment and into tectonically stable crust. Models from both these studies image the most intense conductive features outside the active rift segment, calling into question the magmatic interpretations almost ubiquitously given to conductors within an active volcanic environment.…”
Section: Introductionmentioning
confidence: 95%
“…MT studies of the East African Rift system, one arm of the Afar triple junction (Figure a), differ considerably, with investigations of segments of the Main Ethiopian Rift system alternately advocating for large volumes of upper‐crustal melt (e.g., Didana et al, ; Samrock et al, ) or a complete absence of crustal melt (e.g., Hübert et al, ; Samrock et al, ). Many such studies are based upon short profiles (<50 km) or small arrays located almost entirely within active magmatic rift segments (e.g., Desissa et al, ; Johnson et al, ; Samrock et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Magnetotelluric surveys, used for inferring the Earth's subsurface electrical conductivity, have been conducted at several sites along the EARS (Desissa et al, 2013;Hübert et al, 2018;Johnson et al, 2015;Samrock et al, 2015;Whaler & Hautot, 2006). Resistivity is sensitive to fluid content, allowing the method to identify the presence of partial melt beneath volcanoes (Desissa et al, 2013;Johnson et al, 2015).…”
Section: Implications Of Our Study For Geophysical Imaging Of Peralkamentioning
confidence: 99%
“…Crystal-rich mushes may be disrupted and disaggregated prior to and during eruptions, leading to the accumulation of a range of diverse crystals in the magma, for example, Fish Canyon Tuff (Bachmann et al, 2002), Shiveluch Volcano (Humphreys et al, 2008), Mount Hood (Cooper & Kent., 2014), and Yellowstone (Wotzlaw et al, 2014). Added to these geochemical lines of evidence, geophysical imaging of the upper crust has often failed to detect large bodies of melt beneath active volcanoes (e.g., Hübert et al, 2018;Manzella et al, 2004;Samrock et al, 2015). This has led to suggestions that, in some circumstances, magmas may be stored as melt-poor mush, which is expected to have a low electrical conductivity and low V p /V s ratio (Chu et al, 2010;Miller & Smith, 1999;Steck et al, 1998;Zandt et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…We should also note that the electrical conductivity of Africa in Alekseev et al (2015) is not inferred from magnetotelluric data [(as suggested by De Villiers et al (2016)] but rather combined from the distribution of sediments and a default lithospheric electrical conductivity value. By contrast, geothermal fields in Ethiopia have been extensively studied with magnetotellurics, see e.g., Whaler and Hautot (2006), Desissa et al (2013), Didana et al (2015), Samrock et al (2015), Hübert et al (2018) among others, consistently recovering three orders of magnitude variations in electrical conductivity throughout the Earth's crust (and sometimes lithosphere).…”
Section: Ethiopiamentioning
confidence: 99%